Self-medication among pregnant women attending antenatal clinic at Tertiary Care Center of Nepal - Sah, Ajit Kumar; Giri, Anish; Palikhey, Anjan; Chaurasiya, Roshan Kumar; Yadav, Sudeep Kumar (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Self-medication can cause significant challenges for the individuals and community, especially in women during pregnancy. The aim of this study was to evaluate the prevalence of self-medication among the pregnant women attending antenatal clinic in a tertiary care center of Nepal. Material and Methods: In this cross-sectional study, a total of 225 pregnant women were evaluated for the prevalence of self-medication during pregnancy. Descriptive statistics and chi-square tests were used for statistical analysis of data. Results: The results showed that the prevalence of self-medication, in pregnant women was 41.3%. The leading illness/ symptoms which led to self-medication among pregnant women attending clinic were to relieve headaches 29 (31.2%), cough 21 (22.6%), vomiting 13 (14%), treat fever 11 (11.8%), urinary tract infections 11 (11.8%) and drugs commonly reported for self-medication were paracetamol (30.10%), cough remedies (19.30%), antiemetics (16.13%), analgesics (10.75%). Conclusion: Prevalence of self-medication among pregnant women is high in Nepal. This is a threat to the safety of the developing foetus and the pregnant woman. Therefore, it seems necessary to provide public trainings for all women of reproductive age and train them about the dangers and side effects of self-medication.